Minerals in the nutrition of extremely low birth weight infants - Trindade, Cleide Enoir Petean [UNESP] (FapUNIFESP (SciELO), 2005)
Objective: To review the literature on the role of calcium, phosphorus and trace elements in the nutrition of extremely low birth weight infants, considering their importance for metabolism, bone mineralization and as dietary components. Sources of data: MEDLINE, the Cochrane Database of Systematic Reviews and books on nutrition were searched between 1994 and 2004. Original research studies and reviews were selected. Summary of the findings: Extremely preterm infants are frequently growth-restricted at hospital discharge as a consequence of difficulties in the provision of adequate nutrition. The long-term effects of this growth restriction need to be determined. There is a paucity of studies about the role of minerals, especially micronutrients, in the nutrition of extremely preterm infants. The principal focus of this review was on calcium and phosphorus metabolism, bone mineralization and parenteral and enteral supplementation. A critical evaluation of post-discharge nutrition and its influence upon growth and bone mineralization was presented. Selenium and zinc requirements and the role of selenium as an antioxidant with possible effects on free radical diseases of the preterm infant were discussed. Conclusions: Extremely preterm infants have low mineral reserves and, as a consequence, may have deficiencies in the postnatal period if they do not receive parenteral or enteral supplementation. More studies are needed to elucidate the actual requirements and the appropriate supplementation of micronutrients. There are controversies about the outcome and the influence of post-discharge nutrition on bone disease of prematurity. Copyright © 2005 by Sociedade Brasileira de Pediatria.
Keywords: Calcium; Infant; Micronutrients; Minerals; Nutrition; Preterm; Selenium; calcium; copper; iodine; manganese; mineral; molybdenum; phosphorus; selenium; trace element; zinc; antioxidant activity; artificial milk; bone disease; bone growth; bone mineralization; breast milk; calcium intake; calcium metabolism; child growth; Cochrane Library; enteric feeding; extremely low birth weight; growth retardation; hospital discharge; human; low birth weight; MEDLINE; mineral deficiency; mineral metabolism; nutritional deficiency; nutritional support; parenteral nutrition; phosphate intake; phosphate metabolism; prematurity; review; diet supplementation; drug effect; infant nutrition; newborn; very low birth weight; Calcification, Physiologic; Dietary Supplements; Humans; Infant Nutrition Physiology; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Phosphorus; Trace Elements